Migration and circulation as a way of life for the Wosera Abelam of Papua New Guinea - Curry, George; Koczberski, Gina (1998)
Migration and circulation are now an integral part of the socio-economy of the Wosera Abelam of Papua New Guinea. Since the 1950s large numbers of Wosera Abelam have settled in West New Britain (WNB) towns and government sponsored resettlement schemes. These long-term migrants provide a base in WNB for temporary migrants from the Wosera seeking work or a break from village life. This paper explores the linkages between temporary and long-term migrants in WNB, and between migrants and their relatives remaining in the village. We argue that migration is now a 'way of life' for the Wosera Abelam, and is, to a large extent, underpinned by indigenous (precapitalist) social and economic relations.